The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1590/s0100-204x2005000600006
|View full text |Cite
|
Sign up to set email alerts
|

Utilização de calcário em plantio direto e convencional de soja e milho em Latossolo Vermelho

Abstract: Os solos de cerrado apresentam alta acidez e alumínio tóxico, por isso é necessário aplicar calcário para obter boas produtividades das culturas de grãos. O objetivo deste trabalho foi estudar os efeitos da calagem e de formas de aplicação do calcário na correção da acidez de um Latossolo Vermelho, e na produtividade da soja e do milho, cultivados em rotação, nos sistemas de plantio convencional (aração e gradagem) e de plantio direto (sem preparo). Plantas de cobertura foram cultivadas de forma intercalada: m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0
13

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 14 publications
3
5
0
13
Order By: Relevance
“…Similar findings were reported by Corrêa et al (2009). However, Miranda et al (2005) only observed effects of superficial liming on exchangeable base mobility in the uppermost soil layer of a Typic Hapludox.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Similar findings were reported by Corrêa et al (2009). However, Miranda et al (2005) only observed effects of superficial liming on exchangeable base mobility in the uppermost soil layer of a Typic Hapludox.…”
Section: Resultssupporting
confidence: 87%
“…Maize is considered responsive to soil correction (Miranda et al, 2005;Caires et al, 2006), although genotype may affect tolerance to acidity in soil (Miranda et al, 2005). Oliveira et al (1997) obtained maximum maize yield after applying 6.6 Mg ha -1 limestone in Brazilian Cerrado soil.…”
Section: Resultsmentioning
confidence: 99%
“…Corrêa et al (2008) studied surface liming and the application of silicate as slag and observed that both treatments increased the yield components individually, which increased the soybean yield. Miranda et al (2005) also observed similar results for maize with the superficial application of the correction sources of soil acidity. In fact, the maize yield is correlated to soil pH (Nájera et al, 2015).…”
Section: Discussionsupporting
confidence: 69%
“…Miranda et al (2005), comparando o plantio direto e o convencional, também não observaram diferenças significativas entre os manejos do solo na produtividade.…”
Section: Resultsunclassified